"Three-legged stool" approach, a combined intervention to improve food safety in informal or traditional markets - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
In 2020, pilots with pork slaughterhouses (Vietnam) and pork sellers in traditional markets (Cambodia) were completed. The approach involved low-cost investments combined with training to improve food safety (changes in microbial contamination). Results are unpublished. Not yet reached new stage in 2020 for the other value chain/country pilots.